Supply of Methionine During Late-Pregnancy Alters Fecal Microbiota and Metabolome in Neonatal Dairy Calves Without Changes in Daily Feed Intake - Elolimy, Ahmed; Alharthi, Abdulrahman; Zeineldin, Mohamed; Parys, Claudia; Helmbrecht, Ariane; Loor, Juan J. (Frontiers in Microbiology, 2019)
To our knowledge, most studies demonstrating the role of manipulating maternal nutrition on hindgut (i.e. large intestine) microbiota in the offspring have been performed in non-ruminants. Whether this phenomenon exists in cattle is largely unknown. Therefore, the objectives of the current study were to evaluate the impact of maternal post-ruminal supply of methionine during late-pregnancy in dairy cows on fecal microbiota and metabolome in neonatal calves, and their association with body development and growth performance during the preweaning period. To achieve this, heifer calves, i.e. neonatal female offspring, born to Holstein cows receiving either a control (CON) diet (n = 13) or CON plus rumen-protected methionine (MET; Evonik Nutrition & Care GmbH) during the last 28 d of pregnancy were used. Fecal samples from heifers were collected from birth until 6 weeks of age, i.e. the preweaning period. Fecal microbiota was analyzed with QIIME 2 whereas fecal metabolites were measured using an untargeted LC-MS approach. At birth, MET heifers had greater (P ≤ 0.05) BW, HH and WH. During the preweaning period, no differences between groups were detected for starter intake (P = 0.77). However, MET heifers maintained greater (P ≤ 0.05) BW, HH and tended (P = 0.06) to have greater WH and average daily gain (ADG) (P = 0.10). Fecal microbiota and metabolome profiles through 42 days of age in MET heifers indicated greater capacity for hindgut production of endogenous antibiotics and enhanced hindgut functionality and health. Enhancing maternal post-ruminal supply of methionine during late-gestation in dairy cows has a positive effect on hindgut functionality and health in their offspring through alterations in the fecal microbiota and metabolome without affecting feed intake. Those alterations could limit pathogen colonization of the hindgut while providing essential nutrients to the neonate. Together, such responses contribute to the ability of young calves to achieve better rates of nutrient utilization for growth.